Asuhan Keperawatan Pada Ny. T dengan Gangguan Sistem Pencernaan: Ileus Obstruksi di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Naila Nur Azizah; Ahmad Zakiudin; Sukirno Sukirno (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The digestive system plays a role in processing food into nutrients so that they can be absorbed and utilized by the body, but it is often found that the digestive system experiences disorders that can be caused by various factors such as infection, inflammation, motility disorders, or even neoplasms (Suryati et al., 2025).One of the diseases caused by digestive system disorders is ileus obstruction, which is a disorder of the digestive system that occurs due to a mechanical blockage in the intestine and is often found in patients with intestinal obstruction. One of the diseases resulting from digestive system disorders isileus obstruction, which is a disorder of the digestive system caused by a mechanical obstruction in the intestines and is commonly found in patients who visit the emergency room. It is estimated that approximately 2-8% and 15% of patients require treatment in the surgical unit (Andi Nailah et al., 2024). Obstructive ileus occurs in the small intestine and can be caused by incarcerated hernia, intussusception, intestinal adhesions or adhesions, ascariasis, volvulus, tumors, or gallstones entering the ileum (Su’un, Gani, & Purnama, 2024). The purpose of this writing is to understand and provide nursing intervention for Mrs. T with a digestive system disorders: a case of ileus obstruction in Mawar 2 ward dr. Soeselo Regional General Hospital, Tegal Regency. The method used in this writing is a descriptive method. From the case review, it was found that the patient's main complaint was pain in the lower right abdomen. Three diagnoses emerged: acute pain, anxiety, and knowledge deficit. Interventions were developed based on SDKI, SLKI, and SIKI, which can be implemented.